2003
DOI: 10.1021/jf020820q
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Degradation of Methyl Iodide by Agrochemicals

Abstract: The fumigant methyl iodide (MeI, iodomethane) is considered a promising alternative to methyl bromide (MeBr) for soil-borne pest control in high-cash-value crops. However, the high vapor pressure of MeI results in emissions of a significant proportion of the applied mass into the ambient air, and this may lead to pollution of the environment. Integrating the application of certain agrochemicals with soil fumigation provides a novel approach to reduce excessive fumigant emissions. This study investigated the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Our recent explorations revealed that some sulfur-based agrochemicals, such as thiourea, which has been proposed for use as a nitrification inhibitor (27)(28)(29), might accelerate the degradation of halogenated fumigants in soil (18). Nitrification inhibitors are a group of agrochemicals used to minimize fertilizer N loss by limiting the rate of formation of nitrate from ammonium.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent explorations revealed that some sulfur-based agrochemicals, such as thiourea, which has been proposed for use as a nitrification inhibitor (27)(28)(29), might accelerate the degradation of halogenated fumigants in soil (18). Nitrification inhibitors are a group of agrochemicals used to minimize fertilizer N loss by limiting the rate of formation of nitrate from ammonium.…”
Section: Introductionmentioning
confidence: 99%
“…The end products N-methylaniline (84%), N,N dimethylaniline (13%), and residual MeI (3%) were identified by gas chromatography-mass spectrometry (GC-MS) after 25 days of incubation. Similarly, Zheng et al (2003) noted that MeI half-life in water was reduced from 108 days in the presence of 1.0 mM concentrations of a range of agricultural fertilizers and nitrification inhibitors. Most significant reductions were observed for sodium diethyldithiocarbamate and ammonium diethyldithiocarbamate, with half-lives of 0.13 and 0.14 days, respectively.…”
Section: Transformation In Aqueous Solutionmentioning
confidence: 90%
“…The authors therefore suggested that the nondegraded plant residues of the potting mix may not have been very effective in inducing MeI degradation. Zheng et al (2003) examined the effects of a range of agricultural fertilizers (oxamide, calcium cyanamide, and urea), and nitrification inhibitors (dicyandiamide, thiourea, 1-allyl-2-thiourea, ammonium thiosulfate, sodium diethyldithiocarbamate, and ammonium diethyldithiocarbamate) on the degradation of MeI in soil. Compared to control soil (half-life of 309 h), they observed that MeI half-life was reduced to between 16 and 227 h across all treatments.…”
Section: Transformation In Soilmentioning
confidence: 99%
See 2 more Smart Citations